Efficient computation of addition-subtraction chains using generalized continued Fractions - Tall, Amadou; Sanghare, Ali Yassin (International Journal of Applied Mathematical Research, 2012)
The aim of this paper is to present a new way of computing short addition-subtraction chains using the generalized continued fractions where subtraction is allowed. We will recover the most used ways of getting addition-subtraction chains. This method is not always optimal but gives minimal chains that are easy to compute.